MANAJEMEN HIPOTERMIA DALAM KEPERAWATAN PERIOPERATIF PADA PASIEN YANG MENJALANI PEMBEDAHAN ABDOMEN: A LITERATURE REVIEW - Pratiwi, Ni Komang Dewi Trisia; Raya, Nyoman Agus Jagat; Puspita, Luh Mira (Coping: Community of Publishing in Nursing, 2021)
Perioperative hypothermia defined as core body temperature lower than 36°C, that occurs in response to induction of anesthesia and surgery procedures. The patients who undergoing abdominal surgery are one of the population that have a high risk for the occurrence perioperative hypothermia. Nurses have a primary role in giving an interventions of hypothermia management in perioperative setting, so that can prevent the other complications. This study aims to know the types of hypothermia management interventions and descriptions of their application in perioperative nursing on patients undergoing abdominal surgery. The writing design used is literature review which include 10 literatures that searched using PubMed, ProQuest, Science Direct and Google scholar databases and have been selected based on inclusion-exclusion criteria with PRISMA flowchart. The results showed that the types of hypothermia management interventions are active warming and passive warming methods. Active warming methods such as maintaining operating room temperature, giving warm fluids, the use of forced air warming, circulating-water mattresses, resistive warming systems, self-warming blanket , and humidification warming systems. Passive warming methods includes using cotton blanket, surgical drapes, and garments that made of reflective composite fabric. The operating room nurses specializing in abdominal surgery have an important role in the active and passive management of hypothermia by preparing the equipment at the preoperative stage and monitoring the effectiveness of the intervention during intraoperative and postoperative.